Phylogeography, Interaction Patterns and the Evolution of Host Choice in Drosophila-Parasitoid Systems in Ryukyu Archipelago and Taiwan - Novković, Biljana (PLoS One, 2015)
Island biotas provide a great opportunity to study not only the phylogeographic patterns of a group of species, but also to explore the differentiation in their coevolutionary interactions. Drosophila and their parasitoids are exemplary systems for studying complex interaction patterns. However, there is a lack of studies combining interaction-based and molecular marker-based methods. We applied an integrated approach combining phylogeography, interaction, and host-choice behavior studies, with the aim to understand how coevolutionary interactions evolve in Drosophila-parasitoid island populations. The study focused on the three most abundant Drosophila species in Ryukyu archipelago and Taiwan: D. albomicans, D. bipectinata, and D. takahashii, and the Drosophila-parasitoid Leptopilina ryukyuensis. We determined mitochondrial COI haplotypes for samples representing five island populations of Drosophila and four island populations of L. ryukyuensis. We additionally sequenced parts of the autosomal Gpdh for Drosophila samples, and the ITS2 for parasitoid samples. Phylogenetic and coalescent analyses were used to test for demographic events and to place them in a temporal framework. Geographical differences in Drosophila-parasitoid interactions were studied in host-acceptance, host-suitability, and host-choice experiments. All four species showed species-specific phylogeographic patterns. A general trend of the haplotype diversity increasing towards the south was observed. D. albomicans showed very high COI haplotype diversity, and had the most phylogeographically structured populations, with differentiation into the northern and the southern population-group, divided by the Kerama gap. Differentiation in host suitability was observed only between highly structured populations of D. albomicans, possibly facilitated by restricted gene flow. Differentiation in host-acceptance in D. takahashii, and host-acceptance and host-choice in L. ryukyuensis was found, despite there being no differentiation in these two species according to molecular markers. Host choice assays show that L. ryukyuensis populations that have had more time to coevolve adapt their behavior to exploit the most suitable host – D. albomicans. L. ryukyuensis parasitoids on border ranges may, on the other hand, benefit from broader host-acceptance, that may facilitate adaptation to uncertain and variable environments. All results indicate that Drosophila-parasitoid populations in the Ryukyu archipelago and Taiwan have different evolutionary trajectories, and coevolve in a dynamic, complex, and local-specific way.